The intestinal functions of PXR and CAR - Ye Feng; Jong-Won Kim; Wen Xie (Pharmacological Research)
Pregnane X receptor (PXR) and constitutive androstane receptor (CAR) are so-called xenobiotic nuclear receptors that play pivotal roles in xenobiotic metabolism and detoxification. Both receptors, highly expressed in the liver and intestine, also have endobiotic functions by regulating the homeostasis of endogenous chemicals. While their hepatic functions are well-documented, the functional roles of PXR and CAR in the gastrointestinal tract are less understood. This review highlights the intestinal functions of PXR and CAR, focusing on their involvement in colon cancer, host-microbiome interactions, inflammation, and gut barrier integrity. PXR exhibits dual roles in colon cancer, acting either as a tumor suppressor by inducing cell-cycle arrest or as a promoter of cancer aggressiveness through activating the FGF19 signaling. CAR, on the other hand, regulates intestinal barrier integrity and immune responses, particularly in the context of inflammatory bowel disease (IBD). Both PXR and CAR interact with gut microbiota, modulating microbial composition and the production of metabolites, such as indole-3-propionic acid (IPA) that influences the gut barrier function and inflammation. Activation of PXR also mitigates intestinal inflammation by antagonizing the NF-κB signaling, while CAR activation affects bile acid metabolism and T-cell homeostasis. These findings underscore the complex and context-dependent roles of PXR and CAR in the intestinal tracts, offering potential therapeutic targets for gastrointestinal diseases.